Climate Change and Wildfire Dynamics in South Korea: A Systematic Review of Research and Policy Implications - Kim, Ji-Soo; Kang, SongHee (Journal of Environmental Policy and Administration, 2024)
This systematic review paper investigates the impact of climate change on wildfire dynamics in South Korea, focusing on changes in wildfire patterns and the adequacy of existing policies. By synthesizing a wide range of research studies, the paper explores how climate factors-such as rising temperatures, altered precipitation patterns, and land conditions-affect wildfire frequency, intensity, and distribution. It systematically reviews existing wildfire management policies, including regional prevention policies, response guidelines, post-fire measures, and broader Korea Forest Service policies. The review identifies key gaps in both research and policy, particularly in adapting wildfire policies to shifting wildfire patterns influenced by climate change. The paper concludes with recommendations for future research and policy development, advocating for a comprehensive, region-specific approach to wildfire policy that considers the ongoing impacts of climate change. KCI Citation Count: 0